Whal does lhe nature sell? A glance aboul lhe nature representations in lhe advertising discourse - Amaral, Marise Basso (2017)
The present article, through the analysis of two advertising samples, tries to point out the use of nature images in the advertising of several products (cars, tires, rnilk, insecticides, shampoos, clothes and shoes). It happens by recognizing that the images of the nature " captured " by the culture of the advertising announcements integrate a symbolic net that produces representations of a nature, sometimes romantic, pure and kind, other prirnitive, inhospitable and distant, and, most of the time, a natureresource, nature-object, negative counterpoint of all that the culture and the consumption can offer. In my opinion, advertising discourse is an important cultural and pedagogic production of our time that te aches us, through its naturalized representations of nature, of man, of race, of woman, of work, of success, how we get along with and we positioned ourselves in the world that surrounds us.